Dinosaurs heading for the museum? factors that caused the decline in the economic status of three community papers in Batangas - Balita, Yvette Libuit 1997-; Tangi, Lucia P.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2019)
This mix of both qualitative and quantitative study analyzed the trends in the financial documents of Headlines News Today, Southern Tagalog Herald, and Sun Star People's Courier-community newspapers in the province of Batangas. To develop a holistic view of the economic status of these newspapers, which is assumed to reflect the status of the 14 Batangas community papers, this study employs the second edition of Vincent Mosco's Political Economy of Communication Theory (2009). This research identified physical environment, socio-political situations, marketing strategies, and rise of social media as the factors that lead to the decline in the economic status of these papers. As a result, these local publications modified their newsroom, layout, and the focus of their staff, extended their workforce, and compromised with subscription packages. These were revealed through analysis of financial statement, research on contexts, and interviews with significant people in the newsroom.
Vita.
Thesis
Includes bibliographical references.
Keywords: Community newspapers -- Social aspects -- Philippines